THE STUDENTS’ SCORES ON THE DIFFERENT INSTITUTIONAL TOEFLS AT THE SIXTH SEMESTER ENGLISH DEPARTMENT STUDENTS OF THE PALANGKA RAYA STATE ISLAMIC COLLEGE - -, Sabarun (Educate, 2012)
ABSTRACT The study attempts to investigate whether there is statistically difference or not on the students’ score between the Deborah’s institutional TOEFL and the Barron’s institutional TOEFL. The study belonged to Ex post facto research. The study was conducted at the sixth semester English department students of Palangka Raya State Islamic College of 2011/ 2012 academic year. The number of the subjects was 62 students. This study was restricted to two focuses on testing: the Deborah’s institutional TOEFL and the Barron’s institutional TOEFL. The research instruments applied in the study were test and documentation. To answer the third research problem, the t test for correlated samples was applied. The research findings showed that, based on the statistical calculation, it was found that the t value was 2.904. Based on the Table of t value, if df was 61, the 5% of significant level of t value was at 1.671 and the 1% of significant level of t value was at 2.390. It could be seen that the empiric t value at 2.904 was higher than the t value theoretic. This could be interpreted that at the 5% and 1% of significant level, there was significant difference on the students’ score between the Deborah’s institutional TOEFL (Mean= 398.63) and the Barron’s institutional TOEFL Mean= 413.92). This meant that Ha stating that there is statistically difference on the students’ score between the Deborah’s institutional TOEFL and the Barron’s institutional TOEFL was accepted and Ho stating that there is no statistically difference on the students’ score between the Deborah’s institutional TOEFL and the Barron’s institutional TOEFL was rejected. It meant that there was statistically difference on the students’ score between the Deborah’s institutional TOEFL and the Barron’s institutional TOEFL. In this sense, the Barron’s institutional TOEFL was easier than the Deborah’s institutional TOEFL. Key Words: Students’ Score, Institutional TOEFL.